Job Demands And Job Resources as Antecedents of Work Engagement Among Inpatient Nurse in X Hospital - Paramina, Quintina; Kusumapradja, Rokiah; Mustikawati, Intan Silviana (Jurnal Health Sains, 2024)
Work engagement within hospitals may be impacted by job demands and job stress, underscoring the necessity to augment work resources as a protective measure. Initial investigations conducted at Hospital X have revealed a deficiency in work engagement, particularly in the absorption aspect. This study seeks to assess the effects of job demands and job resources on work engagement, with job stress serving as a mediating factor. Employing a quantitative survey methodology with a cross-sectional design, the study involved 104 inpatient nurses as participants. The method used is the Three Box Method and statistical analysis. The findings indicate that work engagement escalates with increased job resources, while higher job demands correlate with decreased work engagement. Furthermore, enhancing job resources has the potential to alleviate job stress, whereas elevated job demands are associated with heightened job stress levels. Notably, work engagement diminishes with escalating job stress. Through the mediation of job stress, job resources, and job demands, there is a discernible impact on work engagement.